Earnings Quality: The Moderating Role of CEO's Demographic Backgrounds in Agency Relationships - Karyadi, Enrico Adhanur; Slamet, Kuwat (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2022)
Chief executive officer (CEO) as a company leader plays important role in influencing the relationships with its stakeholder, especially within the perspective of agency relationships. This study aims to examine the effect of bonuses, audit quality, and financial distress on earnings quality to represent potential conflicts in agency relationships as well as the moderating role of CEO demographic backgrounds on those effects. Using the sample of property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2020, this study finds that bonuses and CEO demographic backgrounds are negatively associated with earnings quality, while both audit quality and financial distress are not associated with earnings quality. Audit quality plays an important role in aligning principals and agent interest in firms that are being led by CEO that have risky demographic backgrounds. However, CEO demographic backgrounds fail to moderate the agency conflict that occurs within manager-shareholders (bonuses) and manager-creditors (financial distress) on earnings quality. Future research should explore top management team effects demographic backgrounds on agency relationships. Chief executive officer (CEO) sebagai pemimpin perusahaan berperan penting dalam memengaruhi hubungan dengan pemangku kepentingan, terutama dalam perspektif hubungan keagenan. Penelitian ini bertujuan untuk menguji pengaruh bonus, kualitas audit, dan kesulitan keuangan pada kualitas laba untuk mewakili potensi konflik dalam hubungan keagenan serta peran moderasi latar belakang demografis CEO pada pengaruh tersebut. Dengan menggunakan sampel perusahaan properti dan real estat yang terdaftar di Bursa Efek Indonesia (BEI) dari 2014 hingga 2020, penelitian ini menemukan bahwa bonus dan latar belakang demografis CEO berpengaruh negatif terhadap kualitas laba, sedangkan kualitas audit dan kesulitan keuangan tidak berpengaruh signifikan terhadap kualitas laba. Kualitas audit berperan penting dalam menyelaraskan kepentingan principal dan agent di perusahaan yang dipimpin oleh CEO yang memiliki latar belakang demografis yang berisiko. Akan tetapi, latar belakang demografis CEO gagal memoderasi konflik keagenan yang terjadi antara manajer-pemegang saham (bonus) dan manajer-kreditur (kesulitan keuangan) terhadap kualitas laba. Penelitian selanjutnya diharapkan menyelidiki pengaruh latar belakang demografis tim manajemen puncak pada hubungan keagenan.